2017
DOI: 10.1111/trf.14299
|View full text |Cite
|
Sign up to set email alerts
|

Effect on gene expression of three allelic variants in GATA motifs of ABO, RHD, and RHCE regulatory elements

Abstract: Three new alleles in the ABO, RHD, and RHCE genes consist of single-nucleotide changes within GATA motifs, emphasizing the key role of GATA transcription factors in the expression of blood group genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…1 B) 23 , 24 . As the site includes one transcription factor recognition motif for RUNX1 and two motifs for GATA1/2 25 , 26 , deletion and single-nucleotide substitutions in the RUNX motif in the + 5.8-kb site have been found in individuals with A m , B 3 or B w 26 – 28 , while nucleotide substitutions in the downstream GATA motif of the site have been reported in individuals with B m and A m 25 , 29 , 30 . Thus, erythroid cell-specific regulation of ABO transcription could be dependent upon the + 5.8-kb site and the constitutive ABO promoter 23 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…1 B) 23 , 24 . As the site includes one transcription factor recognition motif for RUNX1 and two motifs for GATA1/2 25 , 26 , deletion and single-nucleotide substitutions in the RUNX motif in the + 5.8-kb site have been found in individuals with A m , B 3 or B w 26 – 28 , while nucleotide substitutions in the downstream GATA motif of the site have been reported in individuals with B m and A m 25 , 29 , 30 . Thus, erythroid cell-specific regulation of ABO transcription could be dependent upon the + 5.8-kb site and the constitutive ABO promoter 23 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Promoter variants affect gene expression and regulation. GATA motifs, which are binding sites for the erythroid-specific transcription factor GATA-1, have been shown to play a role in gene expression [13]. In the Duffy blood group system, a mutation in the GATA-1 binding site of the Duffy gene's promoter region results in the Duffy-null phenotype that prevents gene transcription in erythroid cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have investigated the exon and intron regions of RHD and RHCE but relatively few studies exist on their promoters. Fennell et al found that variants in the GATA-1 binding site at 5 0 UTR-115C of RHD and 5 0 UTR-83T of RHCE showed a significant reduction in RH gene expression [13]. Denomme et al [15]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient transfection experiments have shown that these are indispensable for the regulatory activity of the +5.8-kb site. 6,7,12 Deletion and single nucleotide substitutions in the RUNX motif have been found in individuals with A m , B 3 or B w , 8,9,12 while nucleotide substitutions in the downstream GATA motif have been reported in individuals with B m and A m 7,10,11 During erythroid differentiation of CD34 + cells into erythroid cells in vitro, it has been shown that reduction of RUNX1 and GATA2 corresponds to a decline of ABO expression in later stage, while there is no consistent relationship between ABO and GATA1. 13 Thus, it seems that RUNX1 and GATA2 play more important roles in A-or B-antigen expression during erythroid differentiation.…”
Section: Introductionmentioning
confidence: 99%